Infrastructure and Ops Hour with Sam Newman. - Newman, Sam (O'Reilly Media, Inc., 2022)
Incidents are inevitable in complex systems, but learning from these events shouldn't require assigning blame. Workers on the front lines have much to contribute to a company's understanding of how failures happen-and to how to prevent them from happening in the future. Join us for a special conversation about resilience engineering with Sam Newman and incident analysis pro Jessica DeVita. They'll discuss what resilience engineering is and why it matters for infrastructure and operations in particular, walk you through how to learn from incidents while maintaining your teams' cohesion, and explain how to use that knowledge to drive design decisions with intentionality. They'll spend a few minutes covering the trends that are influencing infrastructure, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Explore the origins of, need for, and challenges around incident analysis See what's coming next for infrastructure and ops This live event is for you because ... You're looking for ways to improve your incident response and engineering environment. You want to learn about the foundations of resilience engineering, a discipline that combines safety science with human factors, and understand why resilience depends more on people than on technology. Recommended follow-up: Read 97 Things Every SRE Should Know (book) Read Incident Metrics in SRE (report) Watch Infrastructure & Ops Superstream Series: SRE Edition (recorded Superstream event).